Discovery of Novel N‑Heterocyclic-Fused Deoxypodophyllotoxin Analogues as Tubulin Polymerization Inhibitors Targeting the Colchicine-Binding Site for Cancer Treatment - Leng, Jiafu; Zhao, Yongjun; Sheng, Ping; Xia, Yuanzheng; Chen, Tingting; Zhao, Shifang; Xie, Shanshan; Yan, Xiangyu; Wang, Xiaobing; Yin, Yong; Kong, Lingyi (Journal of medicinal chemistry, 2022)
Natural products are a major source of anticancer agents and play critical roles in anticancer drug development. Inspired by the complexity-to-diversity strategy, novel deoxypodophyllotoxin (DPT) analogues were designed and synthesized. Among them, compound C3 exhibited the potent antiproliferative activity against four human cancer cell lines with IC50 values in the low nanomolar range. Additionally, it showed marked activity against paclitaxel-resistant MCF-7 cells and A549 cells. Moreover, compound C3 can inhibit tubulin polymerization by targeting the colchicine-binding site of tubulin. Further study revealed that compound C3 could arrest cancer cells in the G2/M phase and disrupt the angiogenesis in human umbilical vein endothelial cells. Meanwhile, C3 remarkably inhibited cancer cell motility and migration, as well as considerably inhibited tumor growth in MCF-7 and MCF-7/TxR xenograft model without obvious toxicity. Collectively, these results indicated that compound C3 may be a promising tubulin polymerization inhibitor development for cancer treatment.